Animals in Sociomaterial Processes: An Alternative to Inferential Processes in Animals' Heads. (February 2023) - van Woerkum, Bas
Mindreading and behaviour-reading depict social cognition as an inferential process, taking place inside the individual. This process consists either of mental state ascription (mindreading) or application of general rules (behaviour-reading). In this paper, I develop an alternative to both views, which focuses not on the processes in the animal's head, but on the sociomaterial processes that animals are in and that organize their ongoing activities. Instead of an individual trying to predict the behaviour of another individual based on inferential abilities, the animal is responsive to affordances and how they are nested within the sociomaterial processes that make up the environment. I argue that this depiction of animal social cognition is preferable, because it is allows us to understand the social abilities of nonhuman animals free from our current understanding of human social cognition.